The effect of laparoscopic and abdominal surgery on the treatment of ectopic pregnancy: a systematic review and meta-analysis - Zhai, Lin; Chen, Yinping; Zhang, Shengzhi (Frontiers in Medicine, 2024)
Objective: To compare the efficacy of laparoscopic surgery (LS) and abdominal surgery (AS) in ectopic pregnancy surgery.Methods: A computer-based search was conducted in several databases like CNKI, Wanfang data, VIP data, China Biology Medicine disc (CBMdisc), PubMed, Cochrane Library, Embase, and others to gather domestic and foreign literature on treating ectopic pregnancy. This search was carried out from the inception of each database until July 2022. The literature review was performed using Endnote X9 software, and the data was analyzed using STATA 15.1 software for the meta-analysis.Results: Eight articles that met the inclusion criteria were included in the study. Meta-analysis showed that laparoscopic group had shorter operation time than abdominal surgery group [SMD=-1.28, 95%CI(-2.02,0.54), P=0.001], less intraoperative bleeding [SMD=-3.06, 95%CI(-3.82,-2.31), P<0.01], postoperative anus exhaust time was shorter [SMD=-2.60, 95%CI(-3.26,-1.93), P<0.01] and hospital stay was shorter [SMD=-1.74, 95%CI(-2.09,-1.39), P<0.01] with few complications [RR=0.22, 95%CI(0.08,0.55), P=0.001].Laparoscopic surgery has more evident advantages in the treatment of patients with ectopic pregnancy because there is no English literature that meets the inclusion criteria; whether laparoscopic surgery in the treatment of ectopic pregnancy has the same efficacy for European and American populations needs further study.